[P050] Measurement of the linear attenuation coefficients of breast tissues by synchrotron radiation computed tomography. (August 2018) - Piai, Anna; Donato, Sandro; Brombal, Luca; Arfelli, Fulvia; Bonazza, Debora; Contillo, Adriano; Delogu, Pasquale; Golosio, Bruno; Mettivier, Giovanni; Oliva, Piernicola; Rigon, Luigi; Taibi, Angelo; et al.
Abstract : Purpose: The purpose of this work is the measurement of the linear attenuation coefficients of surgical breast tissues using monochromatic computed tomography (CT) in the energy range from 20 to 38 keV. This research is in the framework of the development of a facility of phase-contrast breast CT with synchrotron radiation (SR). Methods: CT images of three formalin-fixed surgical breast samples, prepared from specimens of mastectomy, are acquired at a SR facility. In order to measure the value of the linear attenuation coefficients from the reconstructed images a calibration is needed. Therefore, three reference materials are used: pure liquid water, ethanol and glycerol. Data for each sample, together with the calibration materials, are acquired with a dead-time-free single-photon-counting CdTe detector with a 60  μ m pixel size. The samples are imaged in continuous rotating mode, delivering 5–20 mGy of mean glandular dose (MGD). Since the SR provides high energy resolution and spatial coherence, phase-contrast imaging techniques can be used and the phase-retrieval algorithm is applied before the FPB reconstruction. To calibrate SR images the XMuDat X-ray database is used: theoretical linear coefficients for water, ethanol and glycerol are calculated at each energy. For each reference material, signal intensity is evaluated as the average of the mean values of homogeneous regions of interest (ROIs) over several slices. Different ROIs are assigned to fat, fibrous and cancer tissues: the mean values and standard deviations, over different slices, are considered in the analysis. Results: A linear dependence between measured and theoretical values of reference materials is verified for each energy and each breast sample image. Linear calibration equations allow the evaluation of linear absorption coefficients of breast tissues (fat, fibrous and cancer tissues). The obtained values are compared to those previously published in literature and a very good agreement is observed. Conclusions: The results demonstrate that phase-contrast SR CT allows the evaluation of linear attenuation coefficients even at low delivered dose. These results are preliminary to an in vivo study, where similar measurements will be done per each patient.